Pengembangan Aplikasi Mobile Berbasis Location-Based Service dalam Mendukung Efisiensi Distribusi Pertanian Padi - Yakti, Ikhwan Kuncoro; Mardhiyyah, Rodhiyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Rice harvest distribution is a critical aspect of maintaining price stability and national food security. However, the traditional distribution system still faces numerous challenges, such as long supply chains, lengthy delivery times, and limited information regarding prices and rice mill locations. These conditions lead to distribution inefficiencies, price fluctuations detrimental to farmers, and a decrease in their welfare. This research focuses on developing a Location-Based Service (LBS) mobile application integrated with a monitoring website to support the efficiency of rice distribution. The developed system is designed to connect farmers, rice mills, and distributors on a single digital platform, enabling a more monitored and integrated distribution process. The mobile application provides features for harvest recording, searching for nearby rice mill locations, real-time market price information, product sales and ordering, transaction logging, agricultural news, and digital payment integration. The monitoring website is intended for relevant agencies to display production and distribution data, progress graphs, and distribution maps of farmers and rice mills. The system was implemented using Flutter for the mobile application, Vue.js for the website, and Firebase Realtime Database as the integrated database, using data from the Cilamaya Wetan Agricultural Technical Service Unit (UPTD). Black Box Testing results indicate that all main system functions such as authentication, product management, ordering, location services, and payment integration are functionally sound and operate according to user requirements. Nevertheless, this testing was limited to technical functionality and did not include usability evaluation or user acceptance in the field. While the traditional distribution process involves 3-4 intermediaries (e.g., farmers, brokers, collectors, mills, large distributors, retailers, end distributors), the developed system offers a design that can shorten this process to only 1-2 intermediaries via a direct channel from farmer to mill, and then to the distributor. Potential analysis indicates that the system could enhance distribution efficiency by reducing intermediaries, improving price transparency, and facilitating easier monitoring by relevant agencies. The mobile application can display rice mill location information on a digital map, accessible to farmers in real-time. This research, therefore, yields a system developed to digitally support rice distribution efficiency. It can serve as a foundation for future research to test the system's implementation in the field and assess its real-world impact on farmer welfare and distribution effectiveness.